Selection of starter cultures for the production of vegetarian kapi, a thai fermented condiment - Wittanalai S. (2014)
Kapi is a traditional fermented shrimp paste that serves as a flavoring in various Thai foods. 7 kapi samples from local markets in Chiang Mai, Trad, Rayong, Chon Buri and Nakhon Sawan, Thailand, were used as a source for the isolation of their bacterial strains. The total viable count of the 7 samples was in the range of 8.48 - 9.30 log cfu/g. A total of 23 isolates were obtained, 10 of which had the ability to produce both proteolytic and amylase activity and these were selected to produce vegetarian kapi using mung bean protein as a substrate. Among the 10 strains, isolate RY1 which was identified as Bacillus subtilis by 16s rDNA analysis, was selected to be the starter culture due to its ability to produce the highest total quantities of nitrogen (110.07 ± 2.76 g/kg), free amino acids (7.92 ± 1.34 mg/g) as well for its low ammoniacal nitrogen content (5.63 ± 0.20 g/kg). The quality of the vegetarian kapi produced by isolate B. subtilis RY1 was compared to that of the commercial vegetarian kapi samples. There were significant differences (p<0.05) in moisture, protein, pH, free amino acid and ammoniacal nitrogen between the vegetarian kapi produced from B. subtilis RY1 and the commercial vegetarian kapi. In addition, organoleptic evaluation scores showed no significant differences between laboratory vegetarian kapi and commercial vegetarian kapi. With the use of the starter culture B. subtilis RY1, the vegetarian kapi could be produced in a shorter period compared with the commercial vegetarian kapi.